2022
DOI: 10.3390/su14106007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on Construction Work Progress: An On-Site Analysis from the Sarawak Construction Project, Malaysia

Abstract: The spread of the COVID-19 pandemic has impacted the economy of the world as well as the construction industry in Malaysia. Many projects were plagued with time and cost overruns due to the COVID-19 pandemic. Site work progress came to an abrupt halt, and productivity stagnated. With that in mind, this study was conducted on the basis of first-hand experience in dealing with the COVID-19 pandemic and how it has affected the construction industry. This study investigated the effects of the COVID-19 pandemic on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The pandemic has caused significant disruptions in the construction industry, leading to project suspensions, delays, labor impacts, time and cost overruns, and financial consequences (Zakaria & Singh, 2021;Gara, Zakaria, Aminudin, Yahya, Sam, Loganathan, Munikanan, Yahya, Wahi, & Shamsuddin, 2022). The implementation of movement control orders and standard operating procedures has affected the progress of construction activities (Kamarazaly et al, 2020).…”
Section: Impacts Of Covid-19mentioning
confidence: 99%
“…The pandemic has caused significant disruptions in the construction industry, leading to project suspensions, delays, labor impacts, time and cost overruns, and financial consequences (Zakaria & Singh, 2021;Gara, Zakaria, Aminudin, Yahya, Sam, Loganathan, Munikanan, Yahya, Wahi, & Shamsuddin, 2022). The implementation of movement control orders and standard operating procedures has affected the progress of construction activities (Kamarazaly et al, 2020).…”
Section: Impacts Of Covid-19mentioning
confidence: 99%
“…Despite the wealth of existing literature on various facets of the Malaysian construction industry, several research gaps continue to persist (Chang and Kumar, 2021;Gara et al, 2022). These gaps underscore the significance of undertaking this study:…”
Section: Introductionmentioning
confidence: 97%
“…Recently, the fast-track projects have gained popularity amongst the construction industry stakeholders due to the increasing requirements of construction sector (Khoueiry et al, 2013). After COVID-19, future prospect of fast-track projects was greatly realized by the construction industry stakeholders specially on medical care related projects (Gara et al, 2022). Telephonic conversations with construction industry practitioners in the US revealed that new opportunities for fast-track application emerged through construction of medical facilities on accelerated schedule and emergency basis during COVID-19 (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%